A novel Ru/TiO2 hybrid nanocomposite catalyzed photoreduction of CO2 to methanol under visible light. Issue 37 (1st September 2015) - Kumar, Pawan; Joshi, Chetan; Labhsetwar, Nitin; Boukherroub, Rabah; Jain, Suman L.
Abstract : A novel in situ synthesized Ru(bpy)3 /TiO2 hybrid nanocomposite is developed for the photoreduction of CO2 into methanol under visible light irradiation. Abstract : A novel in situ synthesized Ru(bpy)3 /TiO2 hybrid nanocomposite is developed for the photoreduction of CO2 into methanol under visible light irradiation. The prepared composite was characterized by means of SEM, TEM, XRD, DT–TGA, XPS, UV–Vis and FT-IR techniques. The photocatalytic activity of the synthesized hybrid catalyst was tested for the photoreduction of CO2 under visible light using triethylamine as a sacrificial donor. The methanol yield for the Ru(bpy)3 /TiO2 hybrid nanocomposite was found to be 1876 μmol g −1 cat ( ϕ MeOH 0.024 mol Einstein −1 ) that was much higher in comparison with the in situ synthesized TiO2, 828 μmol g −1 cat ( ϕ MeOH 0.010 mol Einstein −1 ) and the homogeneous Ru(bpy)3 Cl2 complex, 385 μmol g −1 cat ( ϕ MeOH 0.005 mol Einstein −1 ).